Body composition of the upper limb associated with hypertension, hypercholesterolemia, and diabetes - Qi, Qianjin; Sun, Kui; Rong, Ying; Li, Zhaoping; Wu, Yixia; Zhang, Di; Song, Shuaihua; Wang, Haoran; Feng, Li (Frontiers in Endocrinology, 2022)
The associations between segmental body composition and metabolic diseases remain equivocal. The aim of this study was to investigate this association, using the example of U.S. adults. This was a cross-sectional study including 12,148 participants from the National Health and Nutrition Examination Survey (NHANES) (2011-2018). Multivariable logistic regression models were used to estimate associations between segmental body composition quartiles of hypertension, hypercholesterolemia, and diabetes. Of the 12,148 participants, 3,569 had hypertension, 5,683 had hypercholesterolemia, and 1,212 had diabetes. After adjusting for potential confounders, increased percent upper limb lean body mass was associated with a lower risk of hypertension, hypercholesterolemia, and diabetes. Increased upper limb fat mass is associated with an increased risk of hypertension, hypercholesterolemia, and diabetes. The same correlations were found in the torso and whole-body composition parameters. We observed that for women, lean mass has a better protective effect on metabolic diseases; for men, increased body fat is associated with greater risk of metabolic disease. These findings suggested that adiposity of the upper limb and torso should be considered when assessing chronic metabolic disease risk using body composition.